Adaptive phenotypic plasticity in a clonal invader. Issue 9 (2nd April 2018) - Verhaegen, Gerlien; McElroy, Kyle E.; Bankers, Laura; Neiman, Maurine; Haase, Martin
Abstract: Organisms featuring wide trait variability and occurring in a wide range of habitats, such as the ovoviviparous New Zealand freshwater snail Potamopyrgus antipodarum, are ideal models to study adaptation. Since the mid‐19th century, P. antipodarum, characterized by extremely variable shell morphology, has successfully invaded aquatic areas on four continents. Because these obligately and wholly asexual invasive populations harbor low genetic diversity compared to mixed sexual/asexual populations in the native range, we hypothesized that (1) this phenotypic variation in the invasive range might be adaptive with respect to colonization of novel habitats, and (2) that at least some of the variation might be caused by phenotypic plasticity. We surveyed 425 snails from 21 localities across northwest Europe to attempt to disentangle genetic and environmental effects on shell morphology. We analyzed brood size as proxy for fitness and shell geometric morphometrics, while controlling for genetic background. Our survey revealed 10 SNP genotypes nested into two mtDNA haplotypes and indicated that mainly lineage drove variation in shell shape but not size. Physicochemical parameters affected both shell shape and size and the interaction of these traits with brood size. In particular, stronger stream flow rates were associated with larger shells. Our measurements of brood size suggested that relatively larger slender snails with relatively large apertures were better adapted to strong flow than counterparts with broader shells and relatively small apertures. In conclusion, the apparent potential to modify shell morphology plays likely a key role in the invasive success of P. antipodarum ; the two main components of shell morphology, namely shape and size, being differentially controlled, the former mainly genetically and the latter predominantly by phenotypic plasticity. Abstract : We investigated whether the morphological variation of the shell in the freshwater snail Potamopyrgus antipodarum is adaptive in NW Europe, where it is invasive and reproducing parthenogenetically. Based on geometric morphometrics and controlling for clonal affiliation, we found that shape and size were related to environmental variables, in particular flow velocity, and had an influence on fecundity.